Prevalence and risk factors associated with gastrointestinal parasites of pet dogs in North-Central Algeria. (July 2022) - Ziam, Hocine; Kelanemer, Rabah; Belala, Rédha; Medrouh, Bachir; Khater, Hanem Fathy; Djerbal, Mouloud; Kernif, Tahar
Abstract: The prevalence and risk factors associated with gastrointestinal parasites in dogs were conducted in Blida, North-Central Algeria. The study was carried out over 131 clinically healthy dogs, from March to June 2019, by coprological methods. Of the 131 collected dogs, 61.07% (n = 80) were found infected by gastrointestinal parasites. Sixty-four dogs were carriers of a single infection with the following parasites Ancylostoma spp (15.27%), Uncinaria spp (14.50%) Toxocara canis (4.58%), Trichuris vulpis (3.82%), Toxascaris leonina (2.29%), Taenia / Echinococcus spp. (2.29%), Mesocestoides spp (0.76%), Cystoisospora spp. (3.05%) and Neospora caninum- like (2.29%). Sixteen dogs harbored mixed infection. Male (OR = 1.18) German shepherds' dogs were more infected (OR = 1.08) by helminthic parasites (OR = 13.64). The frequency of single infections (OR = 6.86) increased with the animal's age (OR = 1.73–3.46). Identifying hookworms, T. canis, and T. vulpis suggests a continuing risk of contamination of pet dogs as a source of human infection with the zoonotic parasites in Blida.